Tren Glow Up Challenge di Masa Pandemi Covid-19 - Rahma Rahma; Nurul Ilmi Idrus (Emik, 2022)
The implementation of large-scale social restrictions (PSBB) by the government as an effort to prevent the transmission of the Corona virus has caused a shift in community activities. Many get bored while staying at home and using social media to entertain themselves. One of the most widely used social media during the pandemic is TikTok application. Lots of interesting content uploaded on TikTok which later became a trending activity, one of which is the trend of Glow Up Challenge. This article explores this trend. This research was conducted virtually, namely on TikTok social media because TikTok was booming during the Covid-19 pandemic and was used to follow this trend by uploading their videos with the hashtag #glowupchallenge. Data was collected using in-depth interview and observation. Interviews were conducted online using the Whatsapp application in the form of chat and voicenotes to find out students' perceptions of the Glow Up Challenge trend, the reasons why many millennials and Generation Z are following this trend, and the impact of this trend on their lives. Observations were made through website that discussed the Glow Up Challenge trend and videos using #glowupchallenge through TikTok social media as well as the appeared comments. The fourteen informants involved in this study were generation Z who observed trend Glow Up Challenge. They are students from various universities in the city of Makassar and outside Makassar, consisting of ten women and four men. The study indicates that the trend Glow Up Challenge is a trend where someone uploads videos that show physical changes in TikTok application. Those who participated in the Glow Up Challenge trend because they were aimed to change their physical appearance for their self confidence; to show others who underestimated them because of their physical appearance that is not in accordance with "social standards"; and to be popular. Those, who follow this trend and succeed in demonstrating their significant physical change through uploaded videos, show the conditions before and after participating in this trend. This significant change challenged others to follow this trend, by using the products shared in the uploaded video. This automatically promotes the products being used by those who follow Glow Up Challenge trend. This benefits the company whose products were promoted. But such promotion was under the control of individual because they are involved in the company products marketing. The more people watch the uploaded video, the more popular one becomes. The trend of Glow Up Challenge has both positive and negative impacts. Positive impacts include motivating people to make physical changes by using self-care products and this is intertwined with the growing economy due to the popularity of self-care products. Meanwhile, the negative impacts of this trend involve the emergence of toxic masculinity, feeling insecurity, the use of fake products for instant result, and the tendency to be consumptive.